ARCHITECTURAL INVOLVEMENT OF BEHAVIORAL AS A STEP IN THE DEVELOPMENT OF COMMUNITY SPACE (Case Studi : Pusat Dakwah Islam (PUSDAI) – West Java) - Septian Tri Margana; Heru Wibowo (Indonesian Journal of Built Environmental and Sustainability, 2019)
ABSTRACT :Islam is the most adhered to religion in Indonesia. However the quality of spiritual communities in Indonesia in particular even large cities inversely proportional to the quantity of the Islamic religions. Along with the development of the times, the modernization that occurred in the community resulting in changes in lifestyle and morals. This has a greater impact on the younger generation who have dynamic characters. But not all young people negative affected from current development. Awareness of religious values began to increase the younger generation. It can be seen from more muslim teen communities attending and holding religious and humanitarian activities. However, it supports the activities of muslim youth inadequate the consequences of this mosque’s downward spiral to have only worship functions and the Muslim youth need to be provided with a positive support facility. It was therefore a community center in the context of behaviour based on islam that can strengthen the spiritual, educational, social, and cultural traditions of the Islamic generation so it can become a sustainable, self-sustaining communit. Keywords : Youth Generation, Architecture, Behavior, Community